Obstetrics by ten teachers. - baker philip; Baker, Philip, 1962-; Kenny, Louise C. (Louise Clare) (London : Hodder Arnold, 2011)
In line with recent curriculum changes, this new edition integrates basic sciences and clinical material to aid a thorough understanding of the underlying disease processes.
Previous ed.: 2006.
Includes bibliographical references and index.
Keywords: Obstetrics; Obstetrics; Pregnancy Complications